Effects of Human Presence and Voice on the Behaviour of Shelter Dogs and Cats: A Preliminary Study - Tuozzi, Adele (Animals (Basel), 2021)
SIMPLE SUMMARY: Environmental enrichment is fundamental for the welfare of shelter animals. This study compared the behaviour of single-housed shelter dogs and cats while being read a book (using a prerecording) in the presence of an unfamiliar human (without direct physical contact) or in its absence. Behaviours such as scratching the door, gaze direction and location in relation to the audio source/human were observed for 10 min. When a human was present, dogs spent longer in their bed and looking at the auditory source, while cats scratched the door and rubbed against the door. In the absence of the human, cats tended to spend more time in the vertical dimension, where the hiding boxes were located. Overall, the presence of a person, combined with auditory enrichment, induced greater interest compared to just an audio stimulation in both shelter dogs and cats. However, some animals showed signs of frustration likely due to not being able to physically interact with the human. Given that dogs that exhibit calmness and cats that scratch the door in the presence of humans and try to attract human attention are more likely to be adopted, auditory enrichment combined with human presence promotes behaviours that may consequentially increase adoption rate. ABSTRACT: Reading books to shelter animals combining auditory enrichment with human presence is increasingly used although its effects on animal welfare have not yet been investigated. This study compared the behaviour of single-housed shelter dogs and cats during a prerecorded reading condition in the absence or presence of an unfamiliar human (without direct physical contact). Fourteen dogs and twenty-one cats were observed in their enclosure in the two conditions in a counterbalanced order. Behaviours such as scratching the door, gaze direction and location in relation to the audio source/human were analysed from video recording for 10 min per condition. Dogs spent more time in their bed (p < 0.047) and looking at the auditory source (p < 0.004) when a human was present. Cats showed door scratching and rubbing when a human was present (p < 0.043), whereas they tended to spend more time in the vertical dimension (p = 0.051), where the hiding boxes were located, during auditory stimulation without a human present. These results show that the presence of a human induces greater interest compared to just audio stimulation in shelter dogs and cats but may induce frustration likely due to not being able to physically interact in some animals.